2011
DOI: 10.1128/jcm.02135-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycobacteria in Solid-Culture Media by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has recently been introduced into the clinical microbiology laboratory as a rapid and accurate method to identify bacteria and yeasts. In this paper we describe our work on the use of MALDI-TOF MS for the identification of mycobacterial isolates. We developed a protocol for protein extraction from mycobacteria and utilized it to construct a database containing 42 clinically relevant type and reference strains of mycobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
176
2
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(187 citation statements)
references
References 22 publications
4
176
2
5
Order By: Relevance
“…Intact cell analysis by MALDI-TOF MS incorporates analysis of all compounds coming from the laser-ionized cell envelopes. A mass spectra fingerprint can be used for diagnostic purposes for mycobacterial cultures (Lotz et al, 2012;Saleeb et al 2011). MS methods are robust, fast, cheap and effective but also require bacteria culturing, which can take between 1 day and 2 months depending on the tested species.…”
Section: Discussionmentioning
confidence: 99%
“…Intact cell analysis by MALDI-TOF MS incorporates analysis of all compounds coming from the laser-ionized cell envelopes. A mass spectra fingerprint can be used for diagnostic purposes for mycobacterial cultures (Lotz et al, 2012;Saleeb et al 2011). MS methods are robust, fast, cheap and effective but also require bacteria culturing, which can take between 1 day and 2 months depending on the tested species.…”
Section: Discussionmentioning
confidence: 99%
“…[13] In our current study, we observed that ethanol inactivation yielded MALDI-TOF spectra of significantly higher quality than spectra derived from TFA inactivation, resulting in better [3,4,9] Brucella melitensis g-irradiation [7] Burkholderia spp. 80% TFA, 30 min [9] Francisella tularensis g-irradiation [7] Mycobacterium tuberculosis 95 C, 30-60 min [13,14] Yersinia pestis 70% ethanol, 60 min [10] identification scoring. These data may be linked to the better wetting properties across spots of 70% ethanol relative to 80% TFA.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial protein extraction for MALDI-TOF mass spectrometry using the BioTyper (v3.1, Bruker Daltonics Inc.) was performed by the NIH Clinical Center microbiology lab using previously described methods (46), instrument settings, and calibration (47,48). BioTyper identification was supplemented by additional mass spectra profiles provided by several NIH-developed databases (46,49,50). Ten of the healthy control R. mucosa strains reported in Figure 1 were identified based solely on the unique colony morphology, UV light reactivity, and Gram stain characteristics that had been observed in the other R. mucosa isolates identified by MALDI-TOF analysis.…”
Section: Methodsmentioning
confidence: 99%